Spatial Visualization Tasks To Support Students' Spatial Structuring In Learning Volume Measurement - Shintia Revina; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo; Frans van Galen (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Many prior researches found that most of students in grade five tended to have difficulty in fully grasping the concept of volume measurement because they have to build their competence in spatial structuring. The unit of volume packing measurement must be integrated and coordinated in three-dimension. On the other hand, it is revealed the errors that students made on the volume measurement tasks with threedimensional cube arrays are related to some aspects of spatial visualization, such as the skill to